Complete chloroplast genome sequence of a major invasive species, crofton weed (Ageratina adenophora). - Xiaojun Nie (Public Library of Science (PLoS), 2012)
Background Crofton weed (Ageratina adenophora) is one of the most hazardous invasive plant species, which causes serious economic losses and environmental damages worldwide. However, the sequence resource and genome information of A. adenophora are rather limited, making phylogenetic identification and evolutionary studies very difficult. Here, we report the complete sequence of the A. adenophora chloroplast (cp) genome based on Illumina sequencing. Methodology/principal findings The A. adenophora cp genome is 150, 689 bp in length including a small single-copy (SSC) region of 18, 358 bp and a large single-copy (LSC) region of 84, 815 bp separated by a pair of inverted repeats (IRs) of 23, 755 bp. The genome contains 130 unique genes and 18 duplicated in the IR regions, with the gene content and organization similar to other Asteraceae cp genomes. Comparative analysis identified five DNA regions (ndhD-ccsA, psbI-trnS, ndhF-ycf1, ndhI-ndhG and atpA-trnR) containing parsimony-informative characters higher than 2%, which may be potential informative markers for barcoding and phylogenetic analysis. Repeat structure, codon usage and contraction of the IR were also investigated to reveal the pattern of evolution. Phylogenetic analysis demonstrated a sister relationship between A. adenophora and Guizotia abyssinica and supported a monophyly of the Asterales. Conclusion We have assembled and analyzed the chloroplast genome of A. adenophora in this study, which was the first sequenced plastome in the Eupatorieae tribe. The complete chloroplast genome information is useful for plant phylogenetic and evolutionary studies within this invasive species and also within the Asteraceae family.